A novel Transformation Model©© for personalized medicine laboratory systems. (January 2010) - McKibben, Linda J; Boone, D Joe; Marchibroda, Janet; Issa, Amalia M
The role of health system laboratories is critical to the appropriate clinical integration of personalized medicine. We conducted semistructured interviews with experts and opinion leaders representing laboratory medicine, health policy and the diagnostics industry, to examine what is known about the real-world effectiveness of health laboratories as organizations. We describe and encourage the wider use of an evidence-based, novel Transformation Model©© to prepare for the future and set goals for a better health system. A collaborative approach appropriately integrates the efficiency and high-quality expertise of the health laboratory system with the transformative vision of the personalized medicine community.